Pembentukan Portofolio Optimal Model Markowitz Menggunakan Metode Sharpe (Studi Kasus Pada Saham Jakarta Islamic Index) - Fiona Melta; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2021)
Investment is the activity of placing funds or money with the aim of making a profit. In addition to profits, investments also have risks that can be minimized by forming an optimal portfolio using the Markowitz Model. The purpose of this study is to determine the combination and weight of funds from each stock that makes up the optimal portfolio and to determine the optimal expected return and risk of the Markowitz model based on the Sharpe Ratio. This study uses stock data of the Jakarta Islamic Index during the period August –November 2020. The results of the analysis of 30 stocks of the Jakarta Islamic Index obtained 5 stocks forming an optimal portfolio with fund weights for each share, namely CTRA 5.32%, INCO 40.78%, SCMA 2.97%, SMGR 0.23%. , and TPIA 50.7% with expected return, portfolio risk and maximum sharpe ratio of 0.3760021%, 0.010933%, and 0.359600991, respectively.